2008
DOI: 10.1016/s1130-6343(08)72834-4
|View full text |Cite
|
Sign up to set email alerts
|

Resultados negativos asociados con la medicación en un servicio de urgencias hospitalario

Abstract: The prevalence of NRM in those who attended the emergency department, the high percentage of avoidability and the cost imposed on the Health Service seem to sufficiently argue a case for the consideration that NRM as a problem which requires the implementation of prevention programmes based on drug-treatment monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 14 publications
1
11
1
11
Order By: Relevance
“…In comparison with other international studies, the costs per case and LOS are about average . However, the calculated hospital costs for Germany are higher in this study than some previous estimates.…”
Section: Discussioncontrasting
confidence: 68%
“…In comparison with other international studies, the costs per case and LOS are about average . However, the calculated hospital costs for Germany are higher in this study than some previous estimates.…”
Section: Discussioncontrasting
confidence: 68%
“…En todo caso es importante señalar que los problemas relacionados con 67 pacientes polimedicados (n = 155) un PRM (60% relacionados con la para identificar (y solucionar) PRM seguridad) en un CS. Barcelona 76 (n = 562) para identificar visitas evitables: 83,9% e ingresos por RNM (Asturias) medicamentos (PRM) no siempre suponen la presencia de daño (reacciones adversas a medicamentos [RAM]) y no siempre implican un uso inadecuado de los medicamentos (las RAM pueden producirse en el uso adecuado del fármaco).…”
Section: El Problema De Los Resultados: Entre La Ausencia De Efectiviunclassified
“…Estas cifras son consistentes con otros estudios que han valorado las visitas a los servicios de urgencias hospitalarios (SUH) [72][73][74][75][76] o los ingresos hospitalarios 77-83 debidos a o relacionados con PRM. Un estudio en un hospital de Barcelona (n = 1.800 pacientes) encontró que el 11,9% de sus ingresos médicos por urgencias se debían a PRM, bien por efectos adversos (50,2%), bien por fracaso terapéutico (42,5%) o intoxicación (3,3%).…”
Section: Problemas Relacionados Con Medicamentos Y Efectos Adversos Eunclassified
“…For sample calculation, national and international studies that had observed the frequency of seeking the hospital emergency service due to medication-related morbidities were considered 6,7,12,18 . Considering the mean number of frequencies of 24.73%, an acceptable error of 9.5% and confidence interval of 95%, the minimum sample size was 78 patients with suspected medication-related morbidity.…”
Section: Methodsmentioning
confidence: 99%
“…MRMs have frequently been the cause of persons seeking emergency services. Studies have pointed out rates ranging from approximately 17 to 40% [6][7][8][9] . The morbidities related to the need for and safety of medications are the most cited in cases that lead to admission to hospital 10 .…”
Section: Introductionmentioning
confidence: 99%